Immune Checkpoint Inhibitors in Hepatocellular Carcinoma: Current Progresses and Challenges - Liu, Hao-Tian; Jiang, Meng-Jie; Deng, Zhu-Jian; Li, Le; Huang, Jian-Li; Liu, Zhen-Xiu; Li, Le-Qun; Zhong, Jian-Hong (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is one of the most common malignant tumor in the world and its incidence is increasing in many countries. In recent years, with the deepening understanding of the immune and pathological mechanisms of HCC, immunotherapy based on the regulation of tumor immune microenvironment has become a new treatment choice for patients with HCC. Immune checkpoint inhibitors (ICIs) targeting programmed death protein-1, programmed death protein-ligand-1, or cytotoxic T-lymphocyte-associated antigen 4 are the most widely used. Instead of general immune-enhancing therapies, ICIs can reactivate anti-tumor immune responses by disrupting co-inhibitory T cell signaling. In this review, the research progress and existing problems of ICIs in the treatment of HCC in recent years are reviewed.